2017
DOI: 10.1186/s13054-017-1798-7
|View full text |Cite
|
Sign up to set email alerts
|

Selepressin, a novel selective vasopressin V1A agonist, is an effective substitute for norepinephrine in a phase IIa randomized, placebo-controlled trial in septic shock patients

Abstract: BackgroundVasopressin is widely used for vasopressor support in septic shock patients, but experimental evidence suggests that selective V1A agonists are superior. The initial pharmacodynamic effects, pharmacokinetics, and safety of selepressin, a novel V1A-selective vasopressin analogue, was examined in a phase IIa trial in septic shock patients.MethodsThis was a randomized, double-blind, placebo-controlled multicenter trial in 53 patients in early septic shock (aged ≥18 years, fluid resuscitation, requiring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 28 publications
(30 reference statements)
0
73
0
1
Order By: Relevance
“…It has been shown that selepressin at an infusion rate of 2.5 ng/kg/minute rapidly replaced norepinephrine while maintaining target MAP and may have improved fluid balance and shortened the time of mechanical ventilation. Further studies of selepressin’s mechanism of action and additional larger randomized controlled trials to investigate its efficacy are needed and ongoing to assess its ability to improve the treatment outcome of patients in septic shock [ 76 ].…”
Section: Vasopressors and Other Agentsmentioning
confidence: 99%
“…It has been shown that selepressin at an infusion rate of 2.5 ng/kg/minute rapidly replaced norepinephrine while maintaining target MAP and may have improved fluid balance and shortened the time of mechanical ventilation. Further studies of selepressin’s mechanism of action and additional larger randomized controlled trials to investigate its efficacy are needed and ongoing to assess its ability to improve the treatment outcome of patients in septic shock [ 76 ].…”
Section: Vasopressors and Other Agentsmentioning
confidence: 99%
“…Many anti-cytokine therapies, such as antibodies that target vascular endothelial growth factor or neutralize lipopolysaccharide signaling, have not shown clinical benefit, likely due to complex, time-dependent, and overlapping pathways. Recent trials involving agents that may tighten vascular barriers, such as those that modulate vasopressin [ 67 , 68 ] and adrenomedullin pathways [ 69 , 70 ], are more promising. It is possible that these therapies may counter-act the systemic signaling that leads to TJ disruption in endothelium and epithelium, although additional translational research is required.…”
Section: Discussionmentioning
confidence: 99%
“…55 A small phase IIb human study has been recently completed, finding selepressin a safe and effective noradrenaline-sparing agent, with potential additional benefits. 56 Finally, angiotensin II also reduced noradrenaline requirements for septic shock patients in the recent ATHOS-3 RCT. 57 As with selepressin, further studies are required to demonstrate mortality and organ function benefits.…”
Section: Corticosteroids In Sepsismentioning
confidence: 96%
“…Selepressin activates V1a receptors even more selectively, with potential to reduce important V2‐mediated effects such as fluid accumulation and vascular leakage . A small phase IIb human study has been recently completed, finding selepressin a safe and effective noradrenaline‐sparing agent, with potential additional benefits . Finally, angiotensin II also reduced noradrenaline requirements for septic shock patients in the recent ATHOS‐3 RCT .…”
Section: Haemodynamic Organ Supportmentioning
confidence: 99%